The Magnitude of Market Power between SCBs and SBUs: the Root Cause of Stagnancy of the Growth in Islamic Banking Industry and Spin-off Policy as its Solution - Rayyani, Wa Ode; Abbas, Ahmad; Ayaz, Mohammad; Idrawahyuni, Idrawahyuni; Wahjono, Sentot Imam (Universitas Islam Negeri Raden Intan Lampung, 2022)
This research aims to explore the magnitude of market power’s effect on the two types of Islamic banks consisting of Sharia Commercial Banks (SCBs) and Sharia Business Units (SBUs) and analyze the spin-off policy. Time-series data, obtained from the banks’ monthly financial statements, were used, and the Lerner index under the level of price and cost was utilized. Independent samples t-test and correlation test were employed as additional tests to analyze data. The starting point of the finding discloses that the mean difference of market power on two types of Islamic banking is significant. It indicates that the type of Islamic banks in Indonesia creates a disparity in the market power between SCBs and SBUs where SCBs show low power, otherwise SBUs is in high power value. A high-power magnitude gained by SBUs continues to be absorbed by the conventional bank as its parents. This process leads the growth of conventional banks to increase greater in the banking industry, while the growth of Islamic banks is stagnant. The additional finding discloses that when the SBU undertakes the spin-off, Islamic banking in Indonesia tends to capture a greater power in the national banking industry.